PC.119 Ethical issues regarding consent to trials involving preterm or sick infants: a systematic review (framework synthesis). (9th June 2014) - Wilman, E; Megone, C; Oliver, S; Duley, L; Gyte, G; Wright, J
Abstract : Background: Recruitment of preterm or sick infants to trials requires approaching parents at a particularly difficult time, often within a tight timescale for making a decision. This raises challenges for the obtaining of valid informed consent to such research. We undertook this systematic review (framework synthesis) of the empirical and theoretical studies on these ethical challenges. Methods: A tentative conceptual framework was developed from standard ethics texts. This informed searches of a range of biomedical and philosophy databases to identify potentially eligible studies. Included studies were summarised and categorised into themes which further modified the conceptual framework. Results: 1024 citations were identified, of which 62 were included: 39 empirical and 23 theoretical. The empiric themes that emerged were: parental views of research; clinician views of research; validity of consent; and different methods for gaining consent. The theoretical themes were; ethical basis of parental informed consent; validity of parental consent; other options for gaining consent; and double standard between consent for treatment and for research. Conclusions: There is clear support from parents and from clinicians for the consent process. Nevertheless, there are practical challenges in approaching and discussing participation in research with parents. Theoretical research may offer insights into how to improve the consent process.